Production of Natural Colorant by Monascus Purpureus FNCC 6008 using Rice and Cassava as Carbon Substrates - Margono, Margono; Paryanto, Paryanto; Hanifa, Vina; Abimanyu, Candra (Universitas Negeri Semarang, 2021)
Consumer recognition of the adverse effects of synthetic colorant has increased awareness in utilizing natural colorants as an alternative. One of them is a microbial colorant and it is already studied for its safety and functional properties in the human body, i.e. hypercholesterolemia, antimicrobial, antioxidant, and anticancer. The functional properties of microbial colorant have driven many kinds of research about natural colorant produced by the microorganism. Monascus pigment is one of the popular red pigment synthesized by mold Monascus purpureus. This research was conducted to investigate the effects of particle size and incubation temperature on color value and water solubility of the natural colorant produced by M. purpureus FNCC 6008 using rice and cassava as carbon substrates. Every experiment was conducted in an erlenmeyer flask filled by 15 g of substrates, sterilized and incubated in an incubator chamber. Three particle sizes of 8, 10, and 16 mesh were employed on the incubation temperatures of 30, 32, and 34 oC for 14 days. Two parameters were measured from the sample to evaluate the results of the fermentation process, i.e. color intensity and water solubility of product. The highest color intensity of 59.6 CVU/gds was obtained from the rice substrate at the particle size of 10 mesh and incubation temperature of 32 oC. That particular fermentation condition resulted in a product with 71.4% product solubility.